2022
DOI: 10.1111/ejh.13877
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pulmonary embolism in cancer and noncancer patients: Prospective cohort study

Abstract: Background: Clinical picture and outcome of incidental pulmonary embolism (iPE) compared to symptomatic pulmonary embolism (sPE) remain unclear.Methods: Demographics, recurrent venous thromboembolism (VTE), mortality, major bleeding, and clinically relevant nonmajor bleeding (CRNMB) were compared between iPE and sPE patients who were followed prospectively at Mayo Thrombophilia Clinic (March 1, 2013 to August 1, 2020).Results: Out of 3576 VTE patients, 1417 (39.6%) had PE: 562 (39.7%) iPE and 855 sPE. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…On the other hand, in the current study, the IPE group had lower PESI scores and less frequent central PE and RV dilation on CT, indicating a less severe form of PE, which was also significantly associated with a lower risk of adverse outcome. For the risk of VTE recurrence in our study, there was no significant difference between IPE and SPE, which was similar to the study by Wysokinska et al 6 These subtle discrepancies in the results the prognostic impact of IPE in noncancer patients need to be validated in future research. Since this retrospective study was conducted with data from a single center, selection bias was inevitable.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, in the current study, the IPE group had lower PESI scores and less frequent central PE and RV dilation on CT, indicating a less severe form of PE, which was also significantly associated with a lower risk of adverse outcome. For the risk of VTE recurrence in our study, there was no significant difference between IPE and SPE, which was similar to the study by Wysokinska et al 6 These subtle discrepancies in the results the prognostic impact of IPE in noncancer patients need to be validated in future research. Since this retrospective study was conducted with data from a single center, selection bias was inevitable.…”
supporting
confidence: 89%
“…Approximately 29% of the patients were diagnosed incidentally with PE, which was somewhat consistent with a Vascular Medicine 28 (5) recent study by Wysokinska et al where IPE accounted for 23% of noncancer patients with PE. 6 These findings suggest that the incidence of IPE could be non-negligible in noncancer patients. Many patients in the IPE group of our study had provoking risk factors, including immobilization, surgery, and trauma.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies demonstrated that patients could develop large asymptomatic pulmonary emboli, but many of these cohort studies were conducted in patients with known risk factors for developing clots (such as immobilisation, surgery, trauma or known malignancy). [5][6][7][8][9][10][11][12][13][14] Furthermore, many studies describe incidental findings of emboli on computed tomography pulmonary angiography (CTPA) scans done (at least in part) for reasons other than investigation of PE. 13,15 As such, there are few data in the literature assessing the incidence of asymptomatic pulmonary emboli in ambulant outpatients with ultrasound-proven lower limb DVT.…”
Section: Introductionmentioning
confidence: 99%
“…PE also vary by its location in the pulmonary arteries, which can range from saddle emboli in the pulmonary trunk to clots in the subsegmental pulmonary artery branches. Previous studies demonstrated that patients could develop large asymptomatic pulmonary emboli, but many of these cohort studies were conducted in patients with known risk factors for developing clots (such as immobilisation, surgery, trauma or known malignancy) 5–14 . Furthermore, many studies describe incidental findings of emboli on computed tomography pulmonary angiography (CTPA) scans done (at least in part) for reasons other than investigation of PE 13,15 .…”
Section: Introductionmentioning
confidence: 99%